Effect of Aquatic Plyometric Training on Motor Ability in Youth Football Players - Shimal Hamad Chomani; Abdulla Majeed Dzai; Karzan Karim Khoshnaw; Marko Joksimovic; Ana Lilic; Arazw Mahmood (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to determine the effect of water plyometric training on such components of motor skills as explosive power, agility and speed in young players. Develop practical recommendations for building a training process to improve the motor skills of athletes. Material and methods: when divided into groups of players was used a parallel randomized method with the creation of experimental and control equal groups of 20 players in each group (age 16.25 ± 1.0 years, height 168 ± 3.0 cm, body weight 61, 03 ± 4.0 kg). The duration of the experimental program was 2 months. The water plyometric training program (APT) was used in the experimental group, while the ground plyometric training program (LPT) was used in the control group. Results. In the experimental group was found to increase the jump in height by 21.05%, long jump - by 8.84%. The experimental group also found a significant increase in dexterity by 9.35% with a significance level less than 0.05, a value of t = 7.19. Dexterity as a physical ability combines many other physical abilities, such as speed, strength, power. In the experimental group was also found a significant increase in speed by 12.50% at a significance level less than 0.05. Conclusions. Plyometric training in the water increased the strength of the muscles of the legs of football players, while the majestic vertical jump increased by 21.05%, and the distance of the horizontal jump - by 8.84%. In addition, for 2 months, the training program contributed to the development of dexterity by 9.35% and an increase in speed by 12.50%. The use of ground plyometric training also improves physical abilities, but with fewer indicators of significant change than plyometric training in water.